The Relationship between Emotional Intelligence and Cool and Hot Cognitive Processes: A Systematic Review - Gutiérrez-Cobo, María José; Cabello, Rosario; Fernández-Berrocal, Pablo (Frontiers in Behavioral Neuroscience, 2016)
Although emotion and cognition were considered to be separate aspects of the psyche in the past, researchers today have demonstrated the existence of an interplay between the two processes. Emotional intelligence (EI), or the ability to perceive, use, understand, and regulate emotions, is a relatively young concept that attempts to connect both emotion and cognition. While EI has been demonstrated to be positively related to well-being, mental and physical health, and non-aggressive behaviors, little is known about its underlying cognitive processes. The aim of the present study was to systematically review available evidence about the relationship between EI and cognitive processes as measured through “cool” (i.e., not emotionally laden) and “hot” (i.e., emotionally laden) laboratory tasks. We searched Scopus and Medline to find relevant articles in Spanish and English, and divided the studies following two variables: cognitive processes (hot vs. cool) and EI instruments used (performance-based ability test, self-report ability test, and self-report mixed test). We identified twenty-six eligible studies. The results provide a fair amount of evidence that performance-based ability EI (but not self-report EI tests) is positively related with efficiency in hot cognitive tasks. EI, however, does not appear to be related with cool cognitive tasks: neither through self-reporting nor through performance-based ability instruments. These findings suggest that performance-based ability EI could improve individuals’ emotional information processing abilities.